Acciones educativas de enfermería al cuidador de pacientes con traqueostomo - Choca Soria, Vanesa Sthefanía (2022)
Abstract: Tracheostomy is a general surgical procedure performed on critically ill patients hospitalized in intensive care units (ICU) requiring prolonged intubation. It consists of opening a hole in the anterior part of the trachea between 2° and 7°. ° ring to secure the airway in patients with pathologies that require mechanical ventilation. This bibliographic review was carried out to identify educational nursing actions focused on the caregiver of patients with tracheostomies. Method: A documentary and descriptive study were carried out, with a mixed approach, in indexed journals, available in Scielo, Dialnet, Scopus, Pubmed, Elsevier, Virtual Health Library, ProQuest, and Google Scholar, of national and international organizations. To unify the criteria of educational actions for the caregiver of the patient with a tracheostomy, the risk factors involved in the home care of the patient with a tracheostomy were identified, and the complications of their home management were determined. With the information obtained, a proposal was developed. Of educational actions, using the NANDA, NOC, and NIC taxonomy. Results: Nursing actions are based on training and teaching the caregiver before hospital discharge, usually a family member with little knowledge. Therefore, the nursing staff will implement resources for teaching and training primary care so that they can be executed. This preparation process must be individualized, frequent, directed, and supervised at home, using technological resources such as telemedicine, telehealth, and phantoms. Finally, it is essential to carry out a pre-assessment on the level of knowledge, preparation, physical, psychosocial, emotional, and cultural aspects of the caregiver and the family since care implies an overload for the caregiver in the short or medium term in terms of physical and mental health, in turn, it becomes a factor that affects the quality of life, generating complications and hospital readmissions. Conclusions: The training assisted by the health personnel during the hospital stay is necessary to facilitate the integration of the patient into his family, to the patient-caregiver role at home, through adequate information, personalized and humanized treatment, as well as follow-up. by the first level of care and the use of technological strategies, can reduce risk factors associated with fulfilling the role and in recovery, through the assessment of needs and the use of scientific evidence applying the NANDA, NOC and NIC guidelines. Keywords: tracheostomy, caregiver, educational actions